The problem of long-term pain control in chronic rheumatic diseases - E. Yu. Polishchuk; A. E. Karateev (Современная ревматология)
Pain is one of the main symptoms and the most distressing manifestation of rheumatic diseases (RD). Currently, non-steroidal anti-inflammatory drugs (NSAIDs) are widely used for the symptomatic treatment of RD in real clinical practice, but the effectiveness and tolerability of their longterm use remain insufficiently studied. Many patients with RD require long-term use of NSAIDs. In this case, the presence of comorbid pathology and risk factors for the development of drug complications should be taken into consideration, so the choice of NSAIDs should be based primarily on considerations of patient safety. Aceclofenac (Aertal®) has a pronounced analgesic potential and a good safety profile, which allows us to recommend it for long-term use.